Analisis Implementasi Kebijakan Pengelolaan Sampah sebagai Imbas Ditutupnya TPA Regional Payakumbuh - Gustina Gustina; Vivi Oktari (Jurnal Akuntan Publik, 2024)
This research analyzes the implementation of Regional Government policy in the form of Payakumbuh Mayor's Instruction Number: 01/Instruction/Wk-Pyk/2023 concerning Waste Management. The method used in this research is a qualitative method, namely a case study approach, observation or observation and in-depth understanding of the phenomenon being studied, documentation and interviews with related parties such as traders in traditional markets, residents around the TPS and cleaning officers from the Payakumbuh City Environmental Service. . The research results show that the main obstacle is the community's unpreparedness for the Regional Government's policy to manage waste independently, as a result of the closure of the Payakumbuh Regional TPA due to the impact of the landslide disaster. Another inhibiting factor is that education about waste management has not been thoroughly provided to the community and the lack of support for the facilities needed as well as the application of sanctions and appreciation to the community in waste management. Adequate training and skills are needed, the application of sanctions and partnerships between local governments with the private sector and other social institutions in the promotion and sale of waste recycling products, so that the community is not only independent in waste management but also helps the government in solving waste handling problems.